Tinjauan Maqashid al-Syari’ah Terhadap Larangan Pelaksanaan ‎Ibadah Shalat Di Tempat Ibadah Di Era Pandemi Covid-19‎ - Atan Herman; Muannif Ridwan (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2023)
This research discusses the issue of the prohibition on the implementation of worship during the Covid-19 pandemic in places of worship by using maqashid al-shari'ah as a guide to answering the problem above. Covid-19 has brought significant changes in various lines of life, including the issue of human servitude to the Khaliq. The purpose of this research is to answer the question of governance of worship during Covid-19. The method of this research is descriptive qualitative by using secondary data as the main reference. Research shows that there are many restrictions from the MUI and the government in overcoming this virus, one of which is by suspending congregational prayers at mosques, both Friday prayers and fardhu prayers five times a day. If seen based on the review of maqasid al-shari'ah, then there is one element that exists in the maqashid, namely preserving life. So that the suspension of congregational prayers at the mosque is an alternative to maintaining the benefit of the community. MUI in each of its fatwa policies stipulates a law based on the Qur'an, as-Sunnah, and also ijtihad which is based on fiqh principles that are relevant to each condition and incorporated in the types of fiqh rules daf'u Aḍ-darurah wa raf'u al-ḥaraj in order to create benefit for all human beings.